Factors related to the internal social capital of elderly-caring social organizations: a cross-sectional study in Chongqing, China - Fuqin Xu; Shuo Ding; Guoqing Liu; Zhengsheng Wang; Benjamin Otsen; Kai Ji; Xin Zheng; Ren Chen (BMC, 2023)
Abstract Background Aging has given birth to the demand for high-quality elderly care service and social organizations (ESOs) are gradually taking on a supportive role in the field of elderly care services.. In view of this, our study is designed to examine influencing factors of social capital within the elderly-caring social organizations. Method The study was conducted in four districts of Chongqing Province and a multi-stage random sampling method was used to sample 80 ESOs as subjects for the research. Through a meticulously crafted questionnaire, we gathered valuable data on internal social capital, basic information about the organization, and other variables. Univariate and Binary Logistic Regression analysis were performed on the data to explore the factors associated with social capital within the elderly-caring social organizations using IBM SPSS version 26.0. Result The results showed that 67(83.8%) OF ESOs surveyed were A-type institutions and 13(16.3%) B-type institutions. Among them, 49(61.3%) institutions covered an area of more than 50m2.The institutions of ≤ 2 years were 33(41.3%), 21(26.3%) were established for ≤ 3 ≤ 8 years, and residual 26(32.5%) were institutions ˃ 8 years old. ESOs that possessed 4-6 management employees were 52.422 times more likely to score high for social support (p<0.05, OR = 52.422). Accommodating special care objects and hiring 16-30 employees were significantly linked to the shared language and shared vision dimension (p<0.001, OR = 0.8) and (p<0.05, OR = 8.672), respectively. and the overall social capital dimension (p<0.01, OR = 0.221) (p<0.05, OR = 5.730). Conclusion ESOs with different basic conditions have different amounts of social capital. Factors such as the presence of special care and volunteer staff, a certain number of full-time staff as well as types of services rendered are accompanied with the higher internal social capital of ESOs.